2021
DOI: 10.1186/s10020-021-00280-9
|View full text |Cite
|
Sign up to set email alerts
|

Maresin 1 protects the liver against ischemia/reperfusion injury via the ALXR/Akt signaling pathway

Abstract: Background Hepatic ischemia/reperfusion (I/R) injury can be a major complication following liver surgery contributing to post-operative liver dysfunction. Maresin 1 (MaR1), a pro-resolving lipid mediator, has been shown to suppress I/R injury. However, the mechanisms that account for the protective effects of MaR1 in I/R injury remain unknown. Methods WT (C57BL/6J) mice were subjected to partial hepatic warm ischemia for 60mins followed by reperfus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…MaR1 increased the population of restorative macrophages, the movement of Nrf2 from the cytoplasm to the nucleus, and decreased NF-κB at nuclear levels [ 15 ]. The hepatoprotective effects of MaR1 on IR liver damage could be related to an activation of the ALXR (lipoxin A4 receptor)/Akt signaling pathway [ 16 ]. In non-alcoholic fatty liver disease (NFLD), MaR1 allows hepatocytes to return to homeostasis, reducing apoptosis and increasing phagocytic activity, which is a cardinal sign of active resolution of inflammation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…MaR1 increased the population of restorative macrophages, the movement of Nrf2 from the cytoplasm to the nucleus, and decreased NF-κB at nuclear levels [ 15 ]. The hepatoprotective effects of MaR1 on IR liver damage could be related to an activation of the ALXR (lipoxin A4 receptor)/Akt signaling pathway [ 16 ]. In non-alcoholic fatty liver disease (NFLD), MaR1 allows hepatocytes to return to homeostasis, reducing apoptosis and increasing phagocytic activity, which is a cardinal sign of active resolution of inflammation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the hepatoprotective effect of maresin-1 was abrogated by pretreatment with Boc2 (lipoxin A4 receptor antagonist), and the hepatoprotective effect of maresin-1 was further reversed by inhibition of Akt. Thus, maresin-1 protected the liver from hepatic ischemia-reperfusion injury mediated by the ALXR/Akt signaling pathway [69].…”
Section: Livermentioning
confidence: 93%
“…Similarly, after screening hundreds of GPCRs, Serhan et al found that MaR1 is a ligand for leucine-rich repeat containing G protein-coupled receptor 6 (LGR6), whereas MaR1 stimulates efferocytosis, enhances phagocytosis, and reduces chemotaxis of polymorphonuclear leukocytes and monocytes/macrophages in LGR6-dependent manners via coupling a Gαs protein to stimulate cAMP ( 4 ). Besides, studies have shown that MaR1 exerts its function via interacting with lipoxin A4 receptor (ALXR) in several inflammatory disease model, and the salutary effect of MaR1 could be blocked by ALXR antagonist ( 18 , 19 ), thus ALXR might be another GPCR for MaR1, although the direct binding of MaR1 to ALXR has not been explored. Furthermore, MaR1 is also considered as an endogenous ligand for nuclear receptor retinoic acid-related orphan receptor α (RORα), thus MaR1 enhances the expression and transcriptional activity of RORα and thereby increases the M2 polarity of liver macrophages ( 20 ).…”
Section: Biosynthesis and Receptors Of Maresinsmentioning
confidence: 99%